2011
DOI: 10.1111/j.1742-1241.2011.02699.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel index by tissue Doppler imaging in patients with advanced heart failure: relation to functional class and prognosis

Abstract: The EAS index, which reflects systolic and diastolic performances, is a highly effective means of differentiating between patients with functional class I-II and those with III-IV. The index also correlates with cardiac mortality and hospitalisation for worsening heart failure, thus providing additional value to conventional echocardiographic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In a prior study, Lee et al . demonstrated that EAS index correlates with NYHA class and may identify subjects with HF at risk for mortality and hospitalization for HF . In a large prospective study, EAS index was an independent predictor of death in the general population even in the subgroup with normal conventional echocardiography .…”
Section: Discussionmentioning
confidence: 93%
“…In a prior study, Lee et al . demonstrated that EAS index correlates with NYHA class and may identify subjects with HF at risk for mortality and hospitalization for HF . In a large prospective study, EAS index was an independent predictor of death in the general population even in the subgroup with normal conventional echocardiography .…”
Section: Discussionmentioning
confidence: 93%
“…[19] Recently, in patients with significant LV dysfunction, EAS index has been considered as an independent predictor of NYHA functional class, and it has been also associated with cardiac mortality and hospitalization for heart failure. [20]…”
Section: Discussionmentioning
confidence: 99%
“…The EAS index is a new, yet increasingly, validated marker of combined LV systolic and diastolic performance . Its use was based on previous reports of the interdependence of myocardial velocities and the assumption that standardizing the E′ wave for the prior S′ wave would be a better measure of LV function than the E′/A′ ratios alone.…”
Section: Discussionmentioning
confidence: 99%
“…The E′/(A′×S′) (EAS) index is a recently described and novel marker of global cardiac function using PWTDI . Its premise is based on the linked responses of LV systolic and diastolic function.…”
mentioning
confidence: 99%
See 1 more Smart Citation